Dechlorination of wastewater from shell-based glucosamine processing by mangrove wetland-derived fungi - Han, Zhiping; Moh, Edward S. X.; Santos, André L. S.; Barcellos, Iuri C.; Peng, Yuanhuai; Huang, Weicong; Ye, Jianzhi (Frontiers in Microbiology, 2023)
Wastewater from processing crustacean shell features ultrahigh chloride content. Bioremediation of the wastewater is challenging due to is difficult as the high chloride ion content, making it inhospitable for makes it difficult for most microorganisms to survive and growth. In this study, mangrove wetland-derived fungi were first tested for their salt tolerance, and the highly tolerant isolates were cultured in shrimp processing wastewater and the chloride concentration was monitored. Notably, the filamentous fungal species Aspergillus piperis could remove over 70% of the chloride in the wastewater in within three days, with the fastest biomass increase (2.01 times heavier) and chloride removal occurring between day one to and two. The chloride ions were sequestered into the fungal cells. The Ggenome of this fungal species containeds Cl -conversion enzymes, which may have contributed to the ion removal. The fungal strain iswas found to be of low virulence in low virulent in larval models and could serve as a starting point for further , and may work as a starting strain for considerations into bioremediation of shell processing wastewater, and promotinge the development of a green technology in the shell processing industry.